EFFECTS OF CATION DISTRIBUTION ON SUPEREXCHANGE INTERACTION IN COBALT FERRITES - NA, JG; LEE, TD; PARK, SJ; TANG, YJ; LUO, HL (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 1995)
The effects of the cation distribution change on the superexchange parameters and magnetic properties of cobalt ferrite powders were investigated. The cation distribution change of cobalt ferrite powders with quenching treatment was confirmed from the Mossbauer experiments. The exchange interaction parameters i.e. J(AA), J(BB) and J(AB), Neel temperature of slow-cooled and quenched CoFe2O4 powders were calculated from the variation of the magnetization with temperature on the basis of the two-sublattice model. With a quenching treatment of CoFe2O4, the thermal magnetization was changed, and this was attributed to the cation distribution change of cobalt ferrites. The absolute values of J(AB) increased with the quenching treatment of CoFe2O4, while those of J(AA) and T-N decreased. The values of J(BB) of cobalt ferrite remained the same with the quenching treatment. This result suggested that the decrease of T-N of CoFe2O4 with quenching may be attributed to the decrease of J(AA).